Long-Range Cost Estimates for Old-Age Insurance - Killingsworth, Charles C.; Schroeder, Gertrude (Quarterly Journal of Economics, 1951)
Introduction, 199. — I. Nature of existing cost estimates, 200. — II. General criticism of cost studies, 202. — III. Level wage assumption, 207. — IV. Conclusion, 212.